Quantifying the Effect of Natural Consolidation and Fluid Discharge on Land Subsidence of the Sidoarjo Mud Volcano, East Java, Indonesia - Bayuaji, Giri; Saepuloh, Asep; Pamumpuni , Astyka; Dedy Wijnarko; Maryudhaningrum, Santika Tristi (UIR PRESS, 2026)
Land subsidence in the Sidoarjo Mud Volcano (SMV) area has been widely recognized as a consequence of sustained mud discharge and progressive subsurface consolidation. Earlier geodetic studies using GPS and InSAR, combined with geological and geomechanical investigations, have demonstrated persistent long‑term ground deformation, widespread flooding, and severe infrastructure damage linked to these processes. This study aims to (1) quantify spatial and temporal subsidence rates, (2) identify the dominant controlling mechanisms, and (3) estimate the relative contributions of fluid discharge and natural consolidation to total subsidence. Surface deformation was derived through time‑series analysis of Sentinel‑1A SAR data using the pair‑wise logic technique differential interferometric synthetic aperture radar (PLT‑D‑InSAR). These results were integrated with one‑dimensional (1D) consolidation modeling based on lithological coring data and mud discharge records. The PLT‑D‑InSAR analysis successfully captured detailed subsidence patterns over a wide area and shows good agreement with GPS observations (R² ≈ 0.82). The combined D‑InSAR, consolidation, and discharge analysis reveals a very strong correlation (R² ≈ 0.97), indicating that subsidence is mainly governed by fluid discharge and consolidation processes. Fluid discharge accounts for approximately 72.2% of the total subsidence, while natural consolidation contributes about 16.5%. The highest subsidence rates are concentrated near the mudflow center and are structurally influenced by the Watukosek and Siring faults. These findings highlight the dominant role of discharge‑induced deformation and provide important constraints for long‑term hazard assessment and land‑use planning in the SMV region.